Protein assemblies in the Arabidopsis thaliana chloroplast compartment - Ditz, Noah; Braun, Hans-Peter; Eubel, Holger (Frontiers in Plant Science, 2024)
Equipped with a photosynthetic apparatus that uses the energy of solar radiation to fuel biosynthesis of organic compounds, chloroplasts are the metabolic factories of mature leaf cells. The first steps of energy conversion are catalyzed by a collection of protein complexes, which can dynamically interact with each other for optimizing metabolic efficiency under changing environmental conditions. For a deeper insight into the organization of protein assemblies and their roles in chloroplast adaption to changing environmental conditions, an improved complexome profiling protocol employing a MScleavable cross-linker is used to stabilize labile protein assemblies during the organelle isolation procedure. Changes in protein:protein interaction patterns of chloroplast proteins in response to four different light intensities are reported. High molecular mass assemblies of central chloroplast electron transfer chain components as well as the PSII repair machinery react to different light intensities. In addition, the chloroplast encoded RNA-polymerase complex was found to migrate at a molecular mass of 8 MDa, well above its previously reported molecular mass. Complexome profiling data produced during the course of this study can be interrogated by interested readers via a webbased online resource (https://complexomemap.de/projects-interaction-chloroplasts).Chloroplasts are metabolically highly active cellular compartments of green plant cells. Static and dynamic protein:protein interactions shape a complex and dynamic molecular machinery consisting of multi-subunit protein assemblies involved in harvesting solar radiation energy, carbon and nitrate fixation, the production of reduced organic compounds, and gene expression, among others. Here we report on an improved protocol for identifying protein:protein interactions on a broad scale. When applied on isolated Arabidopsis chloroplasts, this technique yields new information on the composition and molecular mass of chloroplast protein complexes -such as the PSII repair cycle machinery and the chloroplast encoded RNA polymerase complex -as well as their adaptation to different light intensities.